New insights into combined immunotherapy for hepatocellular carcinoma associated with liver cirrhosis - Liu, Yufan; Cong, Kexin; Li, Qiao; Zhang, Dan; Sheng, Jiyao (Frontiers in Immunology, 2025)
Worldwide, most (80%–90%) hepatocellular carcinomas (HCCs) develop against a background of liver cirrhosis, where chronic inflammation, fibrosis, and immune dysfunction collectively shape an immunosuppressive hepatic microenvironment. Despite significant breakthroughs in HCC treatment with immune-checkpoint inhibitors, objective response rates remain limited in patients with advanced HCC, primarily because of cirrhosis-mediated remodeling of the hepatic immune microenvironment. This review systematically summarizes recent theories and mechanisms by which cirrhosis impairs immunotherapy through reshaping the hepatic immune microenvironment. It also covers alterations in the quantity, function, and metabolism of dendritic cells, T cells, macrophages, and neutrophils. Furthermore, it proposes potential intervention targets and combination therapy strategies aimed at correcting these immune abnormalities, all of which have demonstrated value in basic and translational research. In summary, cirrhosis constitutes the pathogenic foundation of HCC and represents a critical determinant of immunotherapy response. The future integration of immunotherapeutic strategies targeting the cirrhotic immune microenvironment holds promise as a key direction for enhancing immunotherapy efficacy in cirrhosis-associated HCC.